The Adventures of Roderick Random - Smollett, T. (Tobias), 1721-1771 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Adventures of Roderick Random" by T. Smollett is a picaresque novel published in 1748. Born to a Scottish gentleman and cast out by his family, young Roderick Random must survive by his wits alone in eighteenth-century Britain. From London to the West Indies, he encounters malice, deception, and hypocrisy at every turn while pursuing wealthy women and seeking his rightful place as a gentleman. Drawing on Smollett's own naval experience, this satirical tale exposes the brutality and corruption of its age. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Adventures_of_Roderick_Random
Release date is 2003-05-01
Tapio Riikonen and David Widger
Keywords: Sea stories; England -- Fiction; Picaresque literature; Rogues and vagabonds -- Fiction; Sailors -- Fiction; Warships -- Fiction; Scots -- England -- Fiction; Impressment -- Fiction